Advances in Interdisciplinary Practice in Industrial Design Proceedings of the AHFE 2018 International Conference on Interdisciplinary Practice in Industrial Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Chung, WonJoon; Shin, Cliff Sungsoo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides readers with a snapshot of cutting-edge methods and procedures in industrial design, with a particular focus on human-centered and user-experience design, service design, sustainable design and applications of virtual & augmented reality. Reporting on both theoretical and practical investigations aimed at improving industrial design through interdisciplinary collaboration, it covers a wide range of topics - from design strategies to product research and planning, exhibit design, as well as new materials and color research. Based on the AHFE 2018 International Conference on Interdisciplinary Practice in Industrial Design, held on July 21-25, 2018, in Orlando, Florida, USA, the book offers a timely guide for industrial designers, production engineers and computer scientists.
The future of footwear design & lasts: Do we now really need them? -- Trans-disciplinarity as a core value: The Richmond Institute for Design and Innovation -- Utilizing music education methods and concepts to enhance industrial design education -- Methods and tools for 3D measurement of hands and feet -- Collective creativity for teaching -- Emotional evidence: Influences on happiness from the frequent positive visual exposure -- A study on user cognitive and affective information supporting system development for product design -- Cultivating values: A service platform design for the preschool children -- Emotional elements of user experience on autonomous vehicle.
Keywords: Engineering design; Human-machine systems; User interfaces (Computer systems).; Human-computer interaction; Computer-aided engineering; Engineering Design; Interaction Design; User Interfaces and Human Computer Interaction; Computer-Aided Engineering (CAD, CAE) and Design